Philip Roth: the ugly truth prophet in times of hypocrisy and political correctness (Philology, 2020)
During his long career, spanning more than five decades, Philip Roth has published more than thirty novels and several volumes of literary criticism. Vilified and praised, Roth’s work is anything but bland. Perhaps the adjective best describing his work is “controversial”.The reasons why almost every novel of his wreaks havoc in literary circles are two. The first is the author’s uncompromising stance on the issue of truth. Roth questions conventional morality by exposing it as a construct. The second reason is that the author’s policy of preaching the “gospel of truth” generates strong reaction from socially-established moral conventions. The tension generated by the public expectations to comply with the social paradigm and the author’s iconoclastic hostility to hypocrisy is the underlying feature of all of his works.
Keywords: truth; morality; iconoclastic; hypocrisy